An Ideal Model For Recovering National Financial Losses From Corporate Corruption Crimes With Legal Insurance - Paskatu Hardinata; Kiki Kristanto; Novea Elysa Wardhani (IAHN-TP Palangka Raya, 2022)
The APH is reluctant to prosecute companies as perpetrators of criminal activity for a variety of reasons. This means law enforcement remains reluctant to implicate companies as perpetrators in corruption cases. In fact, after the publication of Perm 13 in 2016, there were only 6 companies under suspicion as of 2020. To this condition, the authors try to provide legal ideas related to the ideal model for recovering the state's financial losses due to corruption by legally certain entrepreneurial actors related to the Afdoenings Buiten process concept (out-of-court dispute resolution) approach model.